Perilaku Merokok Terhadap Prestasi Belajar Mahasiswa Polman Bandung - Budiarto, Hanif Azis; Permata, Nia; Indroasyoko, Narwikant; Muhammad, Achmad (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2025)
Student smoking seems to be commonly seen around campuses in Indonesia. However, many studies state that there are negative impacts of smoking on cognitive abilities, physical abilities, health, and so on. This can impact students' ability to study optimally and get the best learning achievements. No study explores the conditions regarding smoking and non-smoking students of Polman Bandung, let alone examining their learning achievements. This research reviews student smokers and non-smokers and their learning achievement. The research method is descriptive qualitative, and questionnaires were distributed to students in May 2023 using a Google Form. There were 207 respondents who filled out the questionnaire, of which 71 were smokers and 136 were non-smokers. The results show that non-smoking students have better academic achievement or GPA than smoking students. It is recommended that campuses minimize the increase in the number of smokers to develop the optimization of students' abilities so that they can improve their learning achievements.